Učestalost kome u službi hitne medicinske pomoći - Banjac, Nada; Aleksić, Nevena; Žana M Maksimović,; Hadžić, Renata; Mihajlović, Dalibor (Scripta Medica, 2022)
Background/Aim: Coma is the most severe disturbance of consciousness from which the patient cannot wake up and in which there is no verbal and motor response or opening of the eyes. The aim of the research was to establish the frequency of occurrence of coma and the aetiology of coma in the Banja Luka Emergency Department (ED). Also, the goal was to analyse the accuracy of the referral diagnosis and potential factors that can help the doctor in making a correct diagnosis.Methods: A retrospective cross-sectional study was conducted. In the ED database, in the period from January to September 2022, all patients diagnosed with coma have been found. The gender and age of the patient, vital parameters, performed diagnostic methods and therapy were recorded. The referral diagnosis, the department to which the patient was referred, as well as the final diagnosis determined in hospital conditions were recorded.Results: In the period from January to September 2022 there were 95 patients who were diagnosed with coma. The average age of the patients was 67.76 ± 16.56 years, there were 56 (58.9 %) men and 39 (41.1 %) women. Of that number, 41 (43.2 %) patients were diagnosed with hypoglycaemic coma and those patients were treated in the field. Out of 54 patients, 32 (59.3 %) patients had a confirmed referral diagnosis, while 22 (40.7 %) patients had another diagnosis established at the hospital. All patients with suspected intracranial bleeding or stroke were correctly diagnosed and adequately referred, while all patients with a confirmed diagnosis of sepsis and shock were incorrectly referred (χ2 = 30.563, p < 0.001).Conclusion: The most frequent were coma caused by hypoglycaemia and coma caused by brain ischaemia and non-traumatic bleeding, which were adequately recognised and treated and/or referred. Coma caused by sepsis and shock of different aetiology was not recognised as such and was referred to a neurologist, where precious time was wasted. In order to reduce errors in the field, it is necessary to pay more attention to the anamnestic data on diseases and perform a somatic and neurological examination adequately.
Keywords: Koma; Diferencijalna dijagnoza; Prehospitalno lečenje; Hitna pomoć